Asparagine and glutamine side-chain conformation in solution and crystal: a comparison for hen egg-white lysozyme using residual dipolar couplings. - Higman, V; Boyd, J; Smith, L; Redfield, C (2004)
Experimental (15)N-(1)H and (1)H-(1)H residual dipolar couplings (RDCs) for the asparagine (Asn) and glutamine (Gln) side chains of hen egg-white lysozyme are measured and analysed in conjunction with (1)N relaxation data, information about chi(1) torsion angles in solution and molecular dynamics simulations. The RDCs are compared to values predicted from 16 high-resolution crystal structures. Two distinct groups of Asn and Gln side chains are identified. The first contains residues whose side chains show a fixed, relatively rigid, conformation in solution. For these residues there is good agreement between the experimental and predicted RDCs. This agreement improves when the experimental order parameter, S, is included in the calculation of the RDCs from the crystal structures. The comparison of the experimental RDCs with values calculated from the X-ray structures shows that the similarity between the oxygen and nitrogen electron densities is a limitation to the correct assignment of the Asn and Gln side-chain orientation in X-ray structures. In the majority of X-ray structures a 180 degrees rotation about chi(2) or chi(3), leading to the swapping of N(delta/epsilon 2) and O(delta/epsilon 1), is necessary for at least one Asn or Gln residue in order to achieve good agreement between experimental and predicted RDCs. The second group contains residues whose side chains do not adopt a single, well-defined, conformation in solution. These residues do not show a correlation between the experimental and predicted RDCs. In many cases the family of crystal structures shows a range of orientations for these side chains, but in others the crystal structures show a well-defined side-chain position. In the latter case, this is found to arise from crystallographic contacts and does not represent the behaviour of the side chain in solution.